A MARVEL-ous Study of How Well Galaxy Shapes Reflect Dark Matter Halo Shapes in Cold Dark Matter Simulations - Blake Keith; Ferah Munshi; Alyson M. Brooks; Jordan Van Nest; Anna Engelhardt; Akaxia Cruz; Ben Keller; Thomas Quinn; James Wadsley (The Astrophysical Journal)
We present a 3D shape analysis of both dark matter (DM) and stellar matter (SM) in simulated dwarf galaxies to determine whether stellar shape traces DM shape. Using 80 central and satellite dwarf galaxies from three simulation suites (“Marvelous Massive Dwarfs,” “Marvelous Dwarfs,” and the “DC Justice League”) spanning stellar masses of 10 ^6 –10 ^10 M _⊙ , we measure 3D shapes through the moment of inertia tensor at twice the effective radius to derive axis ratios ( C / A and B / A ) and triaxiality. We find that stellar shape does follow DM halo shape for our dwarf galaxies. However, the presence of a stellar disk in more massive dwarfs ( M _*  ≳ 10 ^7.5 M _⊙ ) pulls the distribution of stellar C / A ratios to lower values, while in lower-mass galaxies the gravitational potential remains predominantly shaped by DM. Similarly, stellar triaxiality generally tracks DM triaxiality, with this relationship being particularly strong for nondisky galaxies and weaker in disky systems. These correlations are reinforced by strong alignment between the SM and DM axes, particularly in disk galaxies. Further, we find no detectable difference in either SM or DM shapes when comparing two different supernova feedback implementations, demonstrating that shape measurements are robust to different implementations of baryonic feedback in dwarf galaxies. We also observe that a dwarf galaxy’s shape is largely unperturbed by recent mergers. This comprehensive study demonstrates that stellar shape measurements can serve as a reliable tool for inferring DM shapes in dwarf galaxies.